2021
DOI: 10.3389/fpsyt.2021.745406
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impacts of Post-weaning Social Isolation on Nucleus Accumbens Function

Abstract: Adolescence is a period of incredible change, especially within the brain's reward circuitry. Stress, including social isolation, during this time has profound effects on behaviors associated with reward and other neuropsychiatric disorders. Because the Nucleus Accumbens (NAc), is crucial to the integration of rewarding stimuli, the NAc is especially sensitive to disruptions by adolescent social isolation stress. This review highlights the long-term behavioral consequences of adolescent social isolation rearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 131 publications
(227 reference statements)
0
6
0
Order By: Relevance
“…Moreover, it has been shown that neurochemical systems in the NAcc, such as CRF and OT, are critical for partner loss in prairie voles ( Bosch et al, 2016 ), and microglia can also directly interact with reward systems critical for pair bonding ( Loth and Donaldson, 2021 ). As the NAcc has been shown to be an important node for post-weaning-induced alterations ( Bendersky et al, 2021 ), we speculate that changes in microglia in the NAcc play a role in alterations to neuronal circuits and behaviors. Further, it has been reported that post-weaning isolation reduces the size of neurons and volume of the MeA ( Cooke et al, 2000 ), and microglia play a causal role in modulating underlying neurochemical alterations and behavioral outcomes from isolation stress ( Wang H. T. et al, 2017 ; Gong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, it has been shown that neurochemical systems in the NAcc, such as CRF and OT, are critical for partner loss in prairie voles ( Bosch et al, 2016 ), and microglia can also directly interact with reward systems critical for pair bonding ( Loth and Donaldson, 2021 ). As the NAcc has been shown to be an important node for post-weaning-induced alterations ( Bendersky et al, 2021 ), we speculate that changes in microglia in the NAcc play a role in alterations to neuronal circuits and behaviors. Further, it has been reported that post-weaning isolation reduces the size of neurons and volume of the MeA ( Cooke et al, 2000 ), and microglia play a causal role in modulating underlying neurochemical alterations and behavioral outcomes from isolation stress ( Wang H. T. et al, 2017 ; Gong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…This is a critical time point in humans as a significant shift in the bacterial populations of gut microbiota occurs due to children switching to a solid and more varied diet; these and other age-related changes have huge implications on health [ 78 ]. In addition, in social isolation models of initiating neuropsychiatric disorders, the prepubescent period is a key time in behavior development [ 79 , 80 , 81 ]. The gut microbiota produces a large number of compounds that can influence health; most are beneficial [ 82 ], though others can be toxic, and changes in bacterial populations could potentially contribute to an increased risk of neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The current study did not measure the duration of isolation-induced effects, but recent evidence suggests that social isolation and other stressful experiences during adolescence may result in long-term, even permanent changes in neural function (Bendersky et al 2021;Burke et al 2017). In the current study, the mice were isolated for 10-12 weeks, which is a relatively long isolation period, but it is possible that we could have seen more dopaminergic phenotypes develop had we tested later into adulthood.…”
Section: Adolescent Micementioning
confidence: 98%